Digital Technologies in Human Resource Practice in the Post-Pandemic World - Mazurchenko , Anastasiia; Maršíková , Kateřina (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
Technologies as effective digitalization tools have become an integral part of today's business worldwide. The role of digital technology has increased even more in the face of changing working conditions caused by the Covid-19 pandemic. Previous researches indicate that the ability to adapt to the impact of the Covid-19 pandemic depends on their employees' competencies development needed for digital technologies' use at work. A fundamental prerequisite for further digitalization is changing the mindset of people throughout the organization and accepting the new digital technologies in their daily working routines. Secondary data based on answers from nearly 900 C-level executives confirmed that companies responded much faster to implementing technologies and remote working actions during the Covid-19 pandemic. They also believe that these shifts will remain after the crisis than expect a return to precrisis norms (LaBerge et al., 2020). Companies have been making these crisis-related changes with the long term in mind. Therefore, human resource managers in different industries face the challenge of continuing employee training and development to help employees bridge the digital competencies gap and train them on digital tools and technologies and how to use them. The primary purpose of this article is to present the topic of digital technologies in the literature and specify the most often-applied methods and tools for employees' training and development concerning the demands of digitalization and digital technologies' use based on primary and secondary data. Secondary data come from the systematic literature review and show current trends and effects of implementing digital technologies when managing human resources. Primary data collected by authors aimed to map the current digital technologies use among employers in the Czech Republic and Germany. Moreover, to find out the support of employers with technology adoption and training and development methods used to extend digital competencies. The authors collected primary data from Czech employers and employees using the CAWI method in 2020-2021. On the employers' side, 27 representatives from the construction sector, 39 from the automotive sector and ten representatives from banks and insurance companies were involved. On the employees' side, 31 employees from different sectors and 37 from a selected Czech higher education institution participated in the survey. The core set of respondents was also expanded with data on digital readiness collected from 85 employees of a selected German educational institution in 2022. The methods of monitoring, comparison, synthesis, deduction and analysis of scientific literature and secondary data were also applied in this article. The results have confirmed that digital technologies have penetrated daily companies' operations regardless of the economic sector. Likewise, the findings have demonstrated that most employers, who participated in this study, included the topic of competency development in their company's long-term human resource management strategy. From employees' point of view, methods of getting digital competencies and the range of training activities differed, and employees intensified their daily use. The findings of this article have also shown the change in the intensity of digital technologies' use due to the coronavirus and illustrated trends in digital human resource management in the post-pandemic business environment.